Central mucoepidermoid carcinoma of the maxilla developing from a calcifying odontogenic cyst: A rare case report - Megumi Isshiki‐Murakami (Wiley, 2021)
Abstract Intraosseous mucoepidermoid carcinoma of the jaw is a rare lesion that has been suggested to originate from the odontogenic epithelium. We report an unusual case of central mucoepidermoid carcinoma in an 18‐year‐old Japanese man with an odontogenic cyst.